Numerical investigation and comparison for heat transfer coefficient for two eco-friendly Nano refrigerants in horizontal tube - H.Soheel, Ammar; Hashim Mohammad, Karam; H.Ghanim, Ahmed (International Journal of Engineering and Technology, 2018)
This paper presents a numerical investigation and comparison for heat transfer coefficient for eco-friendly refrigerants R134a and R600a with Al2O3 and TiO2 nanoparticles at (1, 2, 3 and 4 %) concentration, flowing through a horizontal tube with a constant wall temperature at (310, 320 and 330 0K) using in vapor compression system. The numerical investigation is simulated by CFD model using FLUENT ANSYS 14.5 software. The numerical results indicate, when increasing the nanoparticles, the heat transfer coefficient of nanorefrigerants increases and the R134a+TiO2 nanorefrigerant was selected an optimal nanorefrigerant used in vapor compression system. Finally, the agreement seems to be acceptable between this study and other studies in literature with MPE 7.82 %.